Experimental study on the utilization of raw rice husks as a partial replacement of sand in the production of paver blocks - Hakim Muganga; Setya Winarno; Fitri Nugraheni (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2024)
This study explores the potential use of raw rice husks as a partial substitute for sand in the production of paver blocks, addressing the increasing demand for concrete and the overuse of natural resources like aggregates. Rice husks, an abundant waste material in Indonesia, were incorporated into paver blocks made from Portland cement, sand, and raw rice husks. The initial mix ratio was 1 part cement to 8 parts sand, with subsequent mixes gradually replacing sand with rice husks in proportions ranging from 0.5 to 2 parts. The paver blocks were mixed, molded, and compacted, and their properties were tested for compressive strength, water absorption, skid resistance, and abrasion resistance. Five different mix variations were tested, and the production costs were analyzed. The findings revealed that increasing the rice husk content reduced compressive strength but improved water absorption, skid resistance, and abrasion resistance. Additionally, higher rice husk content resulted in lower production costs. The optimal mix, consisting of 1 part cement, 7.5 parts sand, and 0.5 parts rice husks, met all Indonesian standards and demonstrated the best performance. Further research is recommended to assess freeze-thaw resistance and enhance the cost-effectiveness and quality of paver production.